2000
DOI: 10.1590/s0100-879x2000000300004
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and biochemical changes in male rat lung after surgical and pharmacological castration

Abstract: The morphology of the rat lung was studied by light microscopy in different situations: after surgical and pharmacological castration and after administration of testosterone to the castrated rat to determine if the androgen is required to maintain the normal morphology of the lung. We also determined the effect of flutamide on the phospholipid composition of both the surfactant and microsomes of the lung. Rats were separated into five groups: I -control non-castrated rats, IIcastrated rats sacrificed 21 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
3
11
0
1
Order By: Relevance
“…41,42 The pathological mechanism was consistent with the findings of this study regarding both the surfactant PC reduction and morphological observation in that several alveolar cavities fused into one, lowering the alveolar number and enlarging the average size. The shortage of pulmonary surfactants can cause alveolar surface tension to increase and the gasÀliquid interface to become disorganised, resulting in damage to the monolayer, septa breaks, and fusion of alveolar cavities.…”
Section: Surfactant Phosphatidylcholinesupporting
confidence: 89%
See 1 more Smart Citation
“…41,42 The pathological mechanism was consistent with the findings of this study regarding both the surfactant PC reduction and morphological observation in that several alveolar cavities fused into one, lowering the alveolar number and enlarging the average size. The shortage of pulmonary surfactants can cause alveolar surface tension to increase and the gasÀliquid interface to become disorganised, resulting in damage to the monolayer, septa breaks, and fusion of alveolar cavities.…”
Section: Surfactant Phosphatidylcholinesupporting
confidence: 89%
“…39 The results obtained in this study regarding lyso-PCs were consistent with previous findings on asthma. 41 Among lung cancer patients, decreased PC(16 : 0/0 : 0), PC(0 : 0/16 : 0), PC(18 : 0/0 : 0), and PC(18 : 1/0 : 0) levels were attributed to cell proliferation, a high metabolic state, and abnormal expression of acyl CoA:lysophosphatidylcholine acyltransferase 1 (LPCAT 1 ), which remodels lyso-PCs. 2).…”
Section: View Article Onlinementioning
confidence: 99%
“…proposed that patients receiving GnRH agonists and orchiectomy were at increased risk of infection as a result of androgen deficiency . Possible underlying explanations include castration‐induced morphological/biochemical changes to respiratory cell membranes, changes in the synthesis, secretion and clearance of phospholipids in pulmonary surfactant, as well as alterations in antibiotic susceptibility and microbial growth . We also had expected the effects of GnRH agonists and orchiectomy to be similar.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ADT with antiandrogens could impair the adaptive immune response through interference with T-cell priming 13. Second, it has also been proposed that androgen deprivation may influence the risk of lower respiratory tract infections via morphological and biochemical changes to the cell membranes within the lung 6 7. In addition, androgen deprivation has been shown to cause changes to the synthesis and secretion of phospholipids in pulmonary surfactant 6 7…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in mice, androgen depletion impaired the adaptive immune response, rendering mice more susceptible to microbial infection 12 13. It was also shown that androgen deprivation may influence the risk of lower respiratory tract infections via morphological and biochemical changes to cell membranes within the lung 6 7…”
Section: Introductionmentioning
confidence: 99%